2023
DOI: 10.1021/acsami.3c06562
|View full text |Cite
|
Sign up to set email alerts
|

Spin-to-Charge Conversion in All-Oxide La2/3Sr1/3MnO3/SrIrO3 Heterostructures

Abstract: Spin injection and spin−charge conversion processes in all-oxide La 2/3 Sr 1/3 MnO 3 /SrIrO 3 (LSMO/SIO) heterostructures with different SIO layer thickness and interfacial features have been studied. Ferromagnetic resonance (FMR) technique has been used to generate pure spin currents by spin pumping (SP) in ferromagnetic (FM) half-metallic LSMO. The change of the resonance linewidth in bare LSMO layers and LSMO/SIO heterostructures suggests a successful spin injection into the SIO layers. However, low values … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 51 publications
2
3
0
Order By: Relevance
“…Reciprocal space maps (not shown, see Ref. [9]) confirmed that, in the range of thickness studied in this work, SIO films are always fully strained with the STO underlying substrate (a STO = 0.3905 nm) [9,10,20]. The observed cell parameters point towards an elastic behavior solely attributed to the in-plane compressive strain imposed by the substrate, consistent with prior reports [9].…”
Section: Influence Of Growth Conditionssupporting
confidence: 89%
See 1 more Smart Citation
“…Reciprocal space maps (not shown, see Ref. [9]) confirmed that, in the range of thickness studied in this work, SIO films are always fully strained with the STO underlying substrate (a STO = 0.3905 nm) [9,10,20]. The observed cell parameters point towards an elastic behavior solely attributed to the in-plane compressive strain imposed by the substrate, consistent with prior reports [9].…”
Section: Influence Of Growth Conditionssupporting
confidence: 89%
“…Furthermore, the literature about unexpected SIO-113 electronic properties, including strange metallicity [11,12] or the anomalous or topological Hall effect, is large [13][14][15]. On the other hand, due to its large spin-orbit coupling, it has also been employed in heterostructures for spin torque or spin-to-charge conversion experiments [16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in a simplified model, the expected V ISHE in the bilayer would be proportional to 𝜉 and the bilayer resistance (R). [6,[59][60][61] We find that the relative increase of R is smaller than the enhancement of V ISHE from 0.49 to 1.21 μV, revealing the increased 𝜉 that is consistent with ST-FMR and SHH results. Furthermore, we show that the V ISHE is further enhanced to 1.49 μV by inserting a thin layer (2 nm) of antiferromagnetic insulator LaFeO 3 (LFO) between La 0.66 Sr 0.33 MnO 3 and SrIr 1-x O 3 , which is likely attributed to the suppression of the shunting effect and may also be contributed by the enhancement of interfacial transparency.…”
Section: Inverse Spin Hall Voltage Of Srir 1-x Osupporting
confidence: 88%
“…The ferromagnetic La 0.66 Sr 0.33 MnO 3 was opted as the spin‐current source layer due to the minimal spin rectification effects as compared to the highly conductive Py. [ 59 ] Considering the lattice mismatch, SrTiO 3 substrate was used to grow La 0.66 Sr 0.33 MnO 3, showing excellent ferromagnetic properties at room temperature (Figure S8, Supporting Information). We further demonstrate that SrIrO 3 on SrTiO 3 substrates also shows the similar structure changes by reducing the growth oxygen partial pressure, further suggesting that the control of Ir vacancies by growth is universal on different substrates (Figure S9, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation